Sinusitis-Induced Orbital Apex Syndrome with Unusual Presentation of Facial Nerve Palsy In HIV-Positive Patient - Fernando Nathaniel; Irawaty Hawari; Yohanes Firmansyah; Dean Ascha Wijaya (Malahayati Nursing Journal, 2023)
ABSTRACT Orbital Apex Syndrome (OAS) is a rare ophthalmological disorder characterized by complex symptoms originating from lesions at the orbital apex. Herein, we report a 60-year-old man with a history of diabetes mellitus and hypertension presented with a swollen left eye and sudden visual loss. He also had nasal symptoms before his admission. Treatment includes broad-spectrum antibiotics and antifungals with additional diabetes management and HIV evaluation. OAS, a severe and uncommon complication of a sinusitis infection, can present with diverse symptoms and cause nerve damage in the orbital apical area. The disease can be easily missed or overlooked when it exhibits atypical symptoms in its initial stages. It is crucial to be vigilant and consider the possibility of complications related to the orbital apex for early detection and appropriate treatment. Keywords: Facial Nerve Palsy, HIV, Orbital Apex Syndrome, Sinusitis